Aggression predicts Cortisol Awakening Response in healthy young adults - Sariñana-González, Patricia; Vitoria-Estruch, Sara; Romero-Martínez, Ángel; Moya-Albiol, Luis (Anales de Psicología / Annals of Psychology, 2015)
Few studies have examined therelationship between the cortisol awakening response (CAR) and aggression inhealthy youth adults. This study analyzes this relationship in 83 women (38 inluteal phase and 45 in follicular phase of menstrual cycle) and 20 men.Salivary-free cortisol measures of the CAR were obtained immediately followingawakening and 30, 45, and 60 minutes afterwards. Additionally, participantscompleted a self-report of aggression. Men presented lower levels of CAR thanwomen in luteal phase. Men were also liable to present more physical aggressionthan women, independently of their menstrual phase. General aggression andspecifically verbal aggression are predictors of CAR in men. In women, verbalaggression predicts CAR during the follicular phase of the menstrual cycle;whereas anger and physical aggression do so during the luteal phase. CAR may beused as a valid marker of proneness to aggression – but must be considered differentlydepending on gender and menstrual cycle of women. This study offers relevantinformation on the hormonal bases of aggression and so contributes to theliterature on alleviating problems related to violence.